Various techniques of grafting in anterior perforation of tympanic membrane: our experience - Raga, Preeti S.; Waghre, Amrith Laal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: The lack of anterior support for the graft frequently leads to graft failure if an underlay method is used whereas anterior blunting is a complication of overlay techniques in the anteriorly located tympanic membrane perforations. The objective of the study was to evaluate the correct surgical technique for the reconstruction of anterior tympanic membrane perforation. Methods: Our prospective study was conducted from January 2011 to December 2013. This study included 39 patients of either sex, 17-56 years of age groups, at Kamineni Institute of Medical Sciences Narketpally, Nalgonda district, Telangana state. Our surgical experience with a) Simplified underlay technique-in small perforations having healthy remnant in10 patients. b) Button hole and slitting the graft- in thin atrophic ring anteriorly in 25 patients. c) Gerlach’ quilting procedure- in inadequate anterior rim in 3 patients and d) Kerr flap-in only anterior rim annulus in 1 patient. Results: All these methods gave 91.96% closure rate, a mean auditory threshold gain of 8.5 dB was achieved at the frequencies tested. Conclusions: Here we describe and promote the various techniques of placing grafts in anterior perforations of tympanic membrane, thereby attaining the aforementioned benefits and reducing the incidence of complications.